Communication Strategy Planning Of Majelis Taklim In Implementation Recitation Program - Idawati, Idawati; Handayani, Benni (UIR Press, 2020)
Majelis Taklim is a Non-Formal Islamic Education Society, as a forum for connecting silaturrahim, intensify ukhuwah Islamiyah, increasing faith and devotion to Allah subhanahu wa ta'ala , and popularize Islamic Da'wah. The purpose of this study is to find out how the Majelis Taklim’s efforts in improving recitation. This study uses a descriptive qualitative method in which the writer describes the efforts of the Majelis Taklim in increasing recitation through interview techniques to woman as a member of Majelis Taklim with a population of 40 person. The sampling technique that using is total sampling techniques.